Rivalitas Saudi-Qatar dan Skenario Krisis Teluk - Broto Wardoyo (Universitas Muhammadiyah Yogyakarta, 2018)
Tensions in the Gulf region between Saudi and its allies against Qatar was marked by the termination of diplomatic relations in the midst 2017. The tension has a quite long history and can be divided into three different phases. Prior to and during the 1990s, their rivalry was mainly centred on border disputes. Later, in the 2000s, hydrocarbon politics played a role and intermingled with border disputes as the central issues of disputes. While in the 2010s, the dispute revolves around regional domination. Within the latter context, Iran plays an influential role in the rivalry between Saudi and Qatar. Hence, the balance of political power between Saudi and Iran would be the most critical determinant factor in the future scenario of this crisis. The efforts to prevent the crisis escalation would require a mediator to limit Iranian involvement.